Etv2 rescues Flk1 mutant embryoid bodies. Issue 7 (30th May 2013) - Rasmussen, Tara L.; Martin, Cindy M.; Walter, Camille A.; Shi, Xiaozhong; Perlingeiro, Rita; Koyano‐Nakagawa, Naoko; Garry, Daniel J.
<x xml:space="preserve">Abstract</x> Independent mouse knockouts of Etv2 and Flk1 are embryonic lethal and lack hematopoietic and endothelial lineages. We previously reported that Flk1 activates Etv2 in the initiation of hematopoiesis and vasculogenesis. However, Flk1 and its ligand VEGF are expressed throughout development, from E7.0 to adulthood, whereas Etv2 is expressed only transiently during embryogenesis. These observations suggest a complex regulatory interaction between Flk1 and Etv2. To further examine the Flk1 and Etv2 regulatory interaction, we transduced Etv2 and Flk1 mutant ES cells with viral integrants that inducibly overexpress Flk1 or Etv2. We demonstrated that forced expression of Etv2 rescued the hematopoietic and endothelial potential of differentiating Flk1 and Etv2 mutant cells. We further discovered that forced expression of Flk1 can rescue that of the Flk1, but not Etv2 mutant cells. Therefore, we conclude that the requirement for Flk1 can be bypassed by expressing Etv2, supporting the notion that disruption of Etv2 expression is responsible for the early phenotypes of the Etv2 and Flk1 mutant embryos. genesis 51:471–480.© 2013 Wiley Periodicals, Inc.